Avaliação do efeito sinérgico da carbonatação e do ataque de cloretos no fenômeno da corrosão das armaduras do concreto - Bandeira, Francisca Joyce dos Santos (2024)
One of the main causes of degradation of reinforced concrete structures is the corrosion of reinforcement, caused by depassivation by carbonation and chloride attack. According to the National Association of Corrosion Engineers, the global cost of corrosion in 2013 was equivalent to 3,4 % of global PIB. It is known that the phenomenon of corrosion occurs due to several factors that act simultaneously and the interactions that occur between these factors should not be neglected. Therefore, the aim of this work is to analyze the synergistic effect of carbonation and chloride attack on the phenomenon of reinforcement corrosion, when the type of cement is the concrete varies. Thus, reinforced concrete specimens (CPs) were manufactured, with three different types of Portland Cement, these being CPIII-32-RS, CPIV-32-RS and CPVARI. Such CPs were subjected to cycles of accelerated degradation, by chloride attack, carbonation and the joint action of the two depassivating agents. Deterioration occurred through immersion and drying cycles, where CPs subjected to chloride attack were exposed to an aggressive sodium chloride solution and dried in a laboratory environment, and CPs subjected to carbonation were immersed in water and sent to a chamber continuously fed with CO2. At each half-cycle, electrochemical variables, corrosion potential (Ecorr), corrosion intensity (Icorr) and ohmic resistance (Rohm) were measured in the reinforced concrete CPs. The electrochemical Linear Polarization Resistance (RPL) technique was used to obtain the corrosion rate (icorr). The depth of carbonation and the chloride content were periodically determined in plain concrete CPs exposed to the same environmental conditions. After the deterioration period, the bars were cleaned and the gravimetric mass loss was determined. It was found that the synergistic effect between carbonation and chlorides promoted a shorter depassivation time of the reinforcement compared to other degradation conditions, as well as higher corrosion rates over time, compared to the single attack. After the 12th saturated cycle, for the CPIII-32-RS CPs, the reinforcement exposed to joint attack showed a corrosion rate approximately 43,71 times greater than the corrosion rate when subjected to chloride attack, and 5,49 times higher than the rate for bars subjected to carbonation. Furthermore, the CPs subjected to the joint action of carbonation and chlorides showed greater loss of gravimetric mass, confirming the results presented by the measurement of electrochemical variables, that the synergy between the degradation agents was more harmful than the individual attack.